Powered wheelchair simulator development: implementing combined navigation-reaching tasks with a 3D hand motion controller. Issue 1 (December 2016) - Tao, Gordon; Archambault, Philippe
Abstract Background Powered wheelchair (PW) training involving combined navigation and reaching is often limited or unfeasible. Virtual reality (VR) simulators offer a feasible alternative for rehabilitation training either at home or in a clinical setting. This study evaluated a low-cost magnetic-based hand motion controller as an interface for reaching tasks within the McGill Immersive Wheelchair (miWe) simulator. Methods Twelve experienced PW users performed three navigation-reaching tasks in the real world (RW) and in VR: working at a desk, using an elevator, and opening a door. The sense of presence in VR was assessed using the iGroup Presence Questionnaire (IPQ). We determined concordance of task performance in VR with that in the RW. A video task analysis was performed to analyse task behaviours. Results Compared to previous miWe data, IPQ scores were greater in the involvement domain (p < 0.05). Task analysis showed most of navigation and reaching behaviours as having moderate to excellent (K > 0.4, Cohen's Kappa) agreement between the two environments, but greater (p < 0.05) risk of collisions and reaching errors in VR. VR performance demonstrated longer (p < 0.05) task times and more discreet movements for the elevator and desk tasks but not the door task. Conclusions Task performance showed poorer kinematic performance in VR than RW but similar strategies. Therefore, the reaching component represents a promising addition to the miWe training simulator, though some limitations must be addressed in future development.